Primary Biliary Cholangitis: advances in management and treatment of the disease. Issue 8 (August 2017) - Invernizzi, Pietro; Floreani, Annarosa; Carbone, Marco; Marzioni, Marco; Craxi, Antonio; Muratori, Luigi; Vespasiani Gentilucci, Umberto; Gardini, Ivan; Gasbarrini, Antonio; Kruger, Paola; Mennini, Francesco Saverio; Ronco, Virginia; et al.
Abstract: Primary Biliary Cholangitis, previously known as Primary Biliary Cirrhosis, is a rare disease, which mainly affects women in their fifth to seventh decades of life. It is a chronic autoimmune disease characterized by a progressive damage of interlobular bile ducts leading to ductopenia, chronic cholestasis and bile acids retention. Even if the disease usually presents a long asymptomatic phase and a slow progression, in many patients it may progress faster toward cirrhosis and its complications. The 10 year mortality is greater than in diseases such as human immunodeficiency virus/Hepatitis C Virus coinfection and breast cancer. Ursodeoxycholic acid is the only treatment available today, but even if effective in counteracting the disease progression for the majority of patients, in approximately 40% is not able to decrease effectively the alkaline phosphatase, a surrogate marker of disease activity. Recently, obeticholic acid received the European Medicines Agency conditional approval, as add on treatment in patients non responders or intolerant to ursodeoxycholic acid. The present paper illustrates the opinion of a working group, composed by clinical pharmacologists, gastroenterologists/hepatologists with specific expertise on Primary Biliary Cholangitis and patient associations, on the state of the art and future perspectives of the disease management. The agreement on the document was reached through an Expert Meeting.